Impact of ISO 9001 Quality Management System Implementation on Organizational Quality Culture and Employee Performance - Saifhul Anuar Syahdan; Mujennah; Budi Artinah (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2021)
In order to increase market share an organization is faced with the challenge of improving quality and flexibility, especially for universities. The quality management system has internationally qualified quality standards according to ISO 9001. The quality culture itself can be measured through employee performance.  The author wants to know the influence of quality management system ISO 9001;2015 which refers to Permen Ristek Dikti No. 44/2015 on the culture of quality and performance of employees at universities in Banjarmasin. This study uses quantitative method with purposive sampling sample selection method. The data collection of this study using questionnaires sent a number of 75 questionnaires at universities in Banjarmasin. The data in this study were analyzed using multiple regression statistics with the help of SPSS. Based on the results of the study concluded that the element of quality management system consisting of organizational commitment, the application of procedures positively affect the culture of quality and performance of employees in the organization, the better the commitment of employees in the organization will improve the culture of quality and performance of employees in the organization. The implementation of procedures is the main requirement in the ISO quality management system, so that the existence of Standard Operational Procedures in organizational activities will build a culture of quality and improve the performance of employees in the organization. This suggests that iso 9001:2015 quality management system can foster a culture of organizational quality and improve employee performance.